Comunicação na maternidade: entre o profissional de saúde e paciente na pandemia da COVID-19 - Saft, Ligia Bechara (2022)
Introduction: in the hospital environment, communication is the fundamental basis for welcoming and humanizing the relationship with the patient. The COVID-19 Pandemic caused by the SARS-CoV-2 virus required the use of personal protective equipment (PPE). The use, for example, of a face mask, can create a communicative barrier and hinder the interaction between healthcare professionals and patients. Objective: to investigate the communication between health professionals and patients in maternity hospitals in the city of São Paulo during the COVID-19 Pandemic. Method: the sample had as an inclusion 7 factor health professionals working in maternity hospitals for at least one year before the beginning of the pandemic (March/2020). The sample ended with 81 subjects, 78 women and 3 men, with a mean age of 41.3 years. Volunteer health professionals answered an online questionnaire, focusing on the characterization of the professional activity, on the investigation of the use of personal protective equipment and its relationship with the various communicative aspects and the validated instrument Screening Index for Voice Disorder (SIVD) with focus on establishing risk for voice disorder. Results: from the sample of 81 subjects, the predominance professional activity (35.8%) was nursing technicians, followed by nurses (24.7%) and speech therapists (18.5%), the researcher's professional activity. The majority (80.2%) stated that communication changed with the use of masks, 72.8% reported the presence of negative aspects in communication, although 66.7% highlighted that this issue did not interfere with patient reception. The main changes in nonverbal and verbal communication with the use of a mask were in the voice (84%), followed by listening (79%) and physical contact (72.8%). Higher voice intensity was scored by 79%, followed by the need for more articulation for 67.9% and slower speech for 65.4%). For 55.6%, communication with a mask made the relationship less humanized. In the SIVD, 79% were not at risk for voice disorders. Conclusion: most health professionals working in maternity hospitals pointed out that there is a difference in communication during the COVID-19 Pandemic. The highlight was communication with face masks